Regional Socioeconomic Deprivation in Germany and Adherence to the 24-h Movement Guidelines among Children and Adolescents - Vivien Suchert; Reiner Hanewinkel; Clemens Neumann; Julia Hansen (MDPI AG, 2023)
To examine the relationship between regional socioeconomic deprivation and adherence to the 24-h movement guidelines among children and adolescents, a cross-sectional study was conducted. A total of 17,433 students aged 9-17 participated in a survey in winter 2021/2022. Daily screen time (ST), moderate-to-vigorous physical activity (MVPA), and sleep behavior were outcome variables. The German Index of Socioeconomic Deprivation (GISD), a regional socioeconomic objective measure, was the exposure variable. Associations between GISD and health behaviors were examined using regression models. Models were adjusted for age, gender, school type, and individual self-reported socioeconomic status (SES). The proportions of meeting the MVPA, ST, and sleep duration guidelines were 14%, 22%, and 34%, respectively. A total of 2.3% met all guidelines. Students from the most deprived communities were half as likely to meet all three guidelines compared to students from the most affluent regions (OR = 0.49 [0.28; −0.03], p = 0.010). There was a consistent relationship between GISD and lower levels of adherence to screen time guidelines (most deprived compared to most affluent: OR = 0.49 [0.38; 0.64], p < 0.001). There was no association between GISD and adherence to sleep time guidelines. We found mixed results for the association between GISD and MVPA. Regional SES appears to be an important factor associated with screen time. Screen time should be limited through intervention programs, especially in disadvantaged areas. Parents should be made aware of their children's increased media consumption. Recommendations for screen time should be clearly communicated, as should the health disadvantages of increased media consumption in childhood and adolescence.